Pengaruh Intensitas Modal Dan Koneksi Politik Terhadap Tax Avoidance Industri Barang Konsumsi - Alvin Hartantio, Estralita Trisnawati (Jurnal Paradigma Akuntansi, 2021)
The purpose of research is to obtain about the impact of capital intensity and political connection towards tax avoidance on manufacture companies in the goods and consumption industry sectors listed on the Indonesia Stock Exchange (IDX) in 2012-2018. This study used 196 samples of manufacture companies in the industrial sector of goods and consumption base on purposive sampling method. The data used are secondary data in the form of financial statements. The analysis model was tested using SPSS software version 25 and SmartPLS version 3.3.2. The rasults showed that capital intensity have no positive and significant effect on tax avoidance and political connections have no connections have no positive and significant effect toward tax avoidance. For further research are expected to adding other independent variables, and not use purposive sampling techniques.